PEMILIHAN TOKO HANDPHONE TERBAIK DI KOTA PEMATANGSIANTAR MENGGUNAKAN METODE ORESTE - Agustian Sinaga; Andri Andri; Mhd Ilham; Muhammad Fadly; Muhammad Irfan (semanTIK, 2018)
This study will discuss the selection of the best handphone stores in Pematangsiantar city. This research was conducted to find out the best handphone shop in Pematangsiantar city according to consumers given to consumers through questionnaires. This study uses the Decision Support System with the Oreste method. The Oreste method is one of the methods of Decision Support Systems that adopts Besson Rank, which is a priority scale approach from each indicator. The data used as alternatives are mobile shop data in Pematangsiantar with a sample of 5 stores with 5 assessment criteria, including Price, Quality on Mobile, Service, Consumer Attractiveness and Store Location. The steps carried out in choosing a mobile shop begin by analyzing the system that is running on the handphone shop, then from the results of the analysis the criteria are weighted on the handphone shop, then an alternative weighting is done at the handphone shop. After that, the results of the alternative weight ranking of the handphone shop are carried out. Based on alternative data and criteria using the Oreste method, it can be concluded that the best mobile shop is Selamat Cellular Shop with Preference Value from Distance Score value of 5.3556. Smaller than the other 4 stores.Keywords— Election, Handphone Stores, Pematangsiantar, Decision Support System, Oreste DOI : 10.5281/zenodo.2527918